Female Representation and Position Based on Facts and Members Views in the European Society of Coloproctology. Issue 3 (7th December 2020) - van Loon, Yu-Ting; Jiménez Rodríguez, Rosa; Keller, Deborah S.; Ioannidis, Argyrios; Zimmerman, David D.E.; Christensen, Peter; Möslein, Gabriela
Abstract : BACKGROUND: There is wide variation in gender distribution in colorectal surgery across different European countries. OBJECTIVE: This study aimed to evaluate female representation, implicit bias, and members' perception on female participation and representation at the European Society of Coloproctology 2017 annual scientific meeting. DESIGN: This was a retrospective mixed-methods cross-sectional observational study. SETTINGS: The study was conducted using data from the 2017 European Society of Coloproctology annual scientific meeting program and attendees. MAIN OUTCOME MEASURES: The primary outcome measure was the percentage of female speakers in the formal program and assessment for implicit bias. Secondary outcomes were the percentage of women attending the conference, the percentage of women serving on committees, and the results of the online survey. METHODS: Female representation was retrospectively quantified by role, session type, and topic. Implicit bias was measured classifying the introductions of speakers by moderators as formal (using a professional title) or informal (using name only), then further stratified by gender. An online survey was disseminated and analyzed to investigate the members' perception as a benchmark analysis. RESULTS: Disparities were found between sexes, with fewer women attending the conference (25%), serving as session chairs (8%), speakers (21%), and on committees (10%) compared with men. There were no differences across sexes regarding the formal or informal introduction. The survey among our members showed that significantly fewer women felt equally endorsed within the society compared with men (33% versus 63%; p < 0.001). LIMITATIONS: The retrospective design with data available to be analyzed was limited by the sessions recorded (27/49) and survey respondents (28%). CONCLUSIONS: Female representation within European Society of Coloproctology as chair, speaker, attendee, and committee member was much lower than male representation, both in absolute numbers and relative to membership. Greater awareness of this disparity and inclusiveness are aims of our society. The impact of these initiatives will be determined by reevaluating these metrics at the 2020 annual meeting. See Video Abstract at http://links.lww.com/DCR/B384 . REPRESENTACIÓN Y POSICIÓN FEMENINA EN LA SOCIEDAD EUROPEA DE COLOPROCTOLOGÍA BASADA EN LOS HECHOS Y LAS OPINIONES DE SUS MIEMBROS: ANTECEDENTES: Existe una amplia variabilidad en la distribución de géneros en la cirugía colorrectal en los diferentes países de Europa. OBJETIVO: Evaluar la representación femenina, el sesgo implícito y la percepción de los miembros sobre la participación y representación femenina en el 12° Congreso científico anual de la Sociedad Europea de Coloproctología. DESIGN: Este fué un estudio observacional retrospectivo de métodos mixtos transversales. AJUSTES: Los análisis se realizaron utilizando los datos del programa cintífico de la reunión y los datos de los presentes en el Congreso de la ESCP en 2017. MEDIDAS PRINCIPALES DE RESULTADOS: La principal medida en el resultado fue el porcentaje de disertantes femeninas en el programa definitivo y la evaluación del sesgo implícito. Los resultados secundarios fueron el porcentaje de mujeres que asistieron a la conferencia, trabajaron en los comités y los resultados de la encuesta informática. METODOS: La representación femenina se cuantificó retrospectivamente según el rol, tipo de sesión y temas. Se midió el sesgo implícito clasificando las introducciones de los disertantes por parte de los moderadores de manera formal (usando un título profesional) o informal (usando solamente el nombre), y luego fueron estratificadas por género. Se difundió y analizó una encuesta informática para investigar la percepción de los miembros como análisis de referencia. RESULTADOS: Se encontraron disparidades de género, con menos mujeres presentes en la conferencia (25%), obrando como presidentes de sesión (8%), como disertantes (21%) y como miembros de comités (10%) comparadas con los hombres. No hubo diferencia entre sexos con respecto a la introducción formal o informal. La encuesta informática entre los miembros mostró significativamente que menos mujeres se sentían respaldadas igualitariamente dentro de la sociedad comparadas con los hombres (33% frente a 63%, p<0.001). LIMITACIONES: Diseño retrospectivo de datos limitados a las sesiones grabadas (27/49) y a los encuestados (28%) disponibles para el análisis. CONCLUSIONES: La representación femenina dentro de la Sociedad Europea de Coloproctología como presidente, disertante, asistente ó como miembro del comité fué mucho menor que la representación masculina, tanto en números absolutos como en relación con la membresía. Crear una mayor conciencia de esta disparidad de inclusión son prioridad en nuestra sociedad. El impacto de estas iniciativas se determinará re-evaluando estas variables en reuniones futuras. Consulte Video Resumen en http://links.lww.com/DCR/B384 .